"Not on the Street Where We Live": walking while trans under a model of sex work decriminalisation. Issue 7 (2nd October 2020) - Easterbrook-Smith, Gwyn L. E.
ABSTRACT: The phenomenon frequently described as "walking while trans" in which transgender women, particularly women of colour, are profiled by police on suspicion of soliciting, is documented as occurring in the USA. In New Zealand, sex work was decriminalised in 2003, yet this mode of harassing transgender women persists—enacted by other members of the public, often associated with self-appointed "concerned citizen" groups. An examination of news media texts from 2009 to 2013 identified narrative categories applied to street sex workers (but particularly transgender workers) in South Auckland, and the concurrent attempts to limit their presence in public space through proposed by-laws. The findings highlight the way societal stigma against sex work is deployed against transgender women, at the same time as transmisogynistic discourses are used to reinforce whorephobia. This article concludes that situating the workers as inherently threatening rhetorically positions workers as interlopers in their own community, and contributes to the campaigns to remove them from public space. In the absence of literal policing, the role of enforcing normative limits on who may inhabit these spaces is taken up by other community members.